Sleep Parameters in Short Daily versus Conventional Dialysis: An Actigraphic Study - Ludimila D’Avila e Silva Allemand; Otávio Toledo Nóbrega; Juliane Pena Lauar; Joel Paulo Russomano Veiga; Einstein Francisco Camargos (International Journal of Nephrology)
Previous studies have observed worse sleep quality in patients undergoing conventional dialysis as compared to daily dialysis. Our aim was to compare the sleep parameters of patients undergoing daily or conventional dialysis using an objective measure (actigraphy). This cross-sectional study was performed in three dialysis centers, including a convenience sample (nonprobability sampling) of 73 patients (36 patients on daily hemodialysis and 37 patients on conventional hemodialysis). The following parameters were evaluated: nocturnal total sleep time (NTST), expressed in minutes; wake time after sleep onset (WASO), expressed in minutes; number of nighttime awakenings; daytime total sleep time (DTST), expressed in minutes; number of daytime naps; and nighttime percentage of sleep (% sleep). The Mini-Mental State Examination and the Beck Depression Inventory were also administered. The mean age was 53.4  ±  17.0 years. After adjustment of confounding factors using multiple linear regression analysis, no difference in actigraphy parameters was detected between the groups: NTST (p=0.468), WASO (p=0.88), % sleep (p=0.754), awakenings (p=0.648), naps (p=0.414), and DTST (p=0.805). Different from previous studies employing qualitative analysis, the present assessment did not observe an influence of hemodialysis modality on objective sleep parameters in chronic renal patients.